Identifying risk factors that contribute to acute mountain sickness - Mahomed, Z; Martin, D; Gilbert, E; Grant, CC; Patricios, J; Motara, F (South African Journal of Sports Medicine, 2015)
Background. Acute mountain sickness (AMS) is an ever-increasing burden on the health sector. With reported incidences of greater than 50%, coupled with the fact that recreational activities at high altitude are gaining increasing popularity, more persons are developing AMS. Physicians are therefore increasingly faced with the task of managing and preventing AMS. Objectives. The pathophysiology of AMS is poorly understood, with little understanding of risk factors for the development of AMS. This research aimed to identify epidemiological and physiological risk factors for development of AMS. Methods. This study is a questionnaire-based study conducted in London and at Everest Base Camp, in which 116 lowlanders were invited to participate and fill in a questionnaire to identify potential risk factors in their history that may have contributed to development of or protection against AMS. Results. A total of 89 lowlanders enrolled in the study. Thirty-seven of the participants had AMS at Everest Base Camp, giving a prevalence of 42%. Of the demographic variables, only weight and body mass index (BMI) were statistically significantly associated with AMS, with those who weighed less or had a lower BMI more likely to get AMS. Previous high-altitude experience was also associated with AMS, with those who had such experience less likely to get AMS. Conclusion. Predicting AMS and furthering our understanding of the pathophysiology of AMS will be of tremendous benefit. Further research is needed in this regard.